A new genus and five new species of the Meconematini (Orthoptera: Tettigoniidae: Meconematinae) - Wang, Hanqiang; Liu, Xianwei; Li, Kai; Fang, Yan (Zootaxa, 2012)
In the present paper, one new genus Allocyrtopsis gen. nov. and 5 new species including 1 new in the genus Neocyrtopsisare described. A key to genera and species are provided. All type specimens are deposited in the SEM (Shanghai Entomological Museum, CAS).